Hetrify: Efficient Verification of Heterogeneous Programs on RISC-V - Li, Yiwei; Yin, Liangze; Dong, Wei; Liu, Jiaxin; Hu, Yanfeng; Li, Shanshan (Proceedings / International Conference on Software Engineering, 2025)
The heterogeneous nature of contemporary software, comprising components like closed-source libraries, embedded assembly snippets, and modules written in multiple programming languages, leads to significant verification challenges. Currently, there are no mature and available methods to effectively address such problems. To bridge this gap, we propose a verification approach capable of effectively verifying heterogeneous programs. This approach is universally applicable. It theoretically supports the verification of any heterogeneous program that can be compiled into binary code, without being constrained by any specific programming language. The approach begins by compiling the entire program or its unverifiable segments into binary format. Under guarantees of semantic equivalence, these binaries are converted into verifiable C code, which can then be verified using existing C verification tools. Based on the RISC-V architecture, we developed the Hetrify tool to implement this verification approach. The tool is supported by rigorous mathematical proofs to ensure operational semantic equivalence between the converted C programs and their original counterparts. To validate our approach, we conducted verification experiments on 130 programs, including 100 assembly programs and 30 large heterogeneous programs with missing critical function source code, demonstrating the effectiveness of our approach.